PERSEPSI WISATAWAN TERHADAP WISATA DANAU MASJID KOTO KARI KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI SEBAGAI SEBUAH PRODUK WISATA - Nasution, Nurul Aini; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to determine tourists' perceptions of Koto Kari Mosque Lake, Kuantan Tengah District, Kuantan Singingi Regency, as a tourism product. Using descriptive quantitative methods, this study examined three aspects of perception: cognitive, affective, and conative. The results indicate that tourists' perceptions are generally good, with the cognitive and conative aspects receiving the highest scores. However, the affective aspect remains low due to dissatisfaction with facilities such as restrooms and supporting information. This study recommends improving facilities, comfort, and service quality to support the development of Koto Kari Mosque Lake as a sustainable tourism destination. Keywords: Koto Kari Mosque Lake, Tourist Perception, Tourism Product, Cognitive, Affective, and Conative Aspects.